2000
DOI: 10.1152/ajpgi.2000.278.4.g635
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of HGF activator inhibitor type 1 but not type 2 along with regeneration of intestinal mucosa

Abstract: Hepatocyte growth factor (HGF) activator inhibitor type 1 (HAI-1) and type 2 (HAI-2) are new Kunitz-type serine protease inhibitors that were recently purified and cloned from the human stomach cancer cell line MKN45 as specific inhibitors against HGF activator. Both proteins contain two Kunitz inhibitor domains and are expressed abundantly throughout the gastrointestinal tract, in addition to the placenta, pancreas, and kidney. In this study, to assess the possible roles of HAI-1 and HAI-2 in the intestinal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 41 publications
(67 reference statements)
5
36
0
Order By: Relevance
“…This observation may be in accordance with a previous study that revealed that regenerating intestinal epithelial cells show enhanced expression of HAI-1/SPINT1 but not HAI-2/ SPINT2. 33 Regarding the mechanism underlying these observations, matriptase hypomorphic mice are also susceptible to DSS colitis, again suggesting important roles for optimal matriptase activity in intestinal epithelial homeostasis and integrity. 21 However, expression of claudin-2, a leaky claudin that was up-regulated in the intestine of matriptase hypomorhic mice, 21 was not apparently enhanced in Hai-1/Spint1-deficient intestine (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This observation may be in accordance with a previous study that revealed that regenerating intestinal epithelial cells show enhanced expression of HAI-1/SPINT1 but not HAI-2/ SPINT2. 33 Regarding the mechanism underlying these observations, matriptase hypomorphic mice are also susceptible to DSS colitis, again suggesting important roles for optimal matriptase activity in intestinal epithelial homeostasis and integrity. 21 However, expression of claudin-2, a leaky claudin that was up-regulated in the intestine of matriptase hypomorhic mice, 21 was not apparently enhanced in Hai-1/Spint1-deficient intestine (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Some represent secreted or membranal proteins while others code for intracellular proteins. Proteins that are secreted, like HAI-2 and syndecan-1 (both of which are overexpressed in several cancers; Bayer-Garner et al, 2000;Dobra et al, 2000;Itoh et al, 2000;Kataoka et al, 2000), are suitable for the development of a noninvasive urine-based diagnostic test for TCC. Alternatively, an RT-PCR-based test on urine samples may be developed for genes coding for intracellular proteins, since the transitional epithelium cells are exfoliated in the urine in both normal and disease conditions (Rotem et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of HAI-1 is enhanced or induced during tissue regeneration and inflammation and may regulate the HGFA-mediated activation of pro-HGF (3,29). Moreover, HAI-1 and its target proteases HGFA and matriptase are implicated in the progression of breast cancer (20,22), hepatocellular carcinoma (30), and ovarian cancer (31).…”
mentioning
confidence: 99%